The Stone and the Wireless : Mediating China, 1861-1906 - Ma, Shaoling, 1980- (Book collections on Project MUSE., 2021)
"The Stone and the Wireless redefines the concept of media to animate the dynamic relations between technics and signification, history and theory, and science and culture in turn-of-the-twentieth century China. Analyzing diplomatic diaries, early science fiction, political and social treatises, the popular press, lithography, photography, and telegrams, Shaoling Ma argues that media do not mediate between this and that entity before first mediating between some version of its already mediated form as discursive representations in texts and images, and the apparently unmediated technical device or process. Insofar as any media history must acknowledge that its very sources are themselves media documents, this book is at its heart a challenge to the epistemological divides between technics and signification, history and theory, science and culture"--